2013
DOI: 10.1111/ijpp.12040
|View full text |Cite
|
Sign up to set email alerts
|

British pharmacists' work-life balance – is it a problem?

Abstract: Pharmacy employers and government should recognise the changing demographic characteristics of the profession and consider what support might be available to the workforce to help alleviate work/life balance problems being experienced by certain groups of pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Regarding professional stressors, respondents' comments ( Table 3) included both external and individual factors, which is consistent with previously published literature. 1,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Regarding the question about what interferes with respondents' ability to meet expectations in their professional lives, 2 other themes emerged, namely (1) health and (2) striving for perfection. Comments related to health, often times related to not having time to maintain a healthy lifestyle, being lonely, suffering anxiety and depression, and mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding professional stressors, respondents' comments ( Table 3) included both external and individual factors, which is consistent with previously published literature. 1,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Regarding the question about what interferes with respondents' ability to meet expectations in their professional lives, 2 other themes emerged, namely (1) health and (2) striving for perfection. Comments related to health, often times related to not having time to maintain a healthy lifestyle, being lonely, suffering anxiety and depression, and mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There is an abundance of reported research that describes pharmacists' job stress, job satisfaction, professional commitment, work motivation, work overload, burnout, and job turnover. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] There is evidence that stress levels are rising for student pharmacists 38,39 and pharmacy residents as well. [40][41][42][43][44] Recent literature showed that 61% of clinical pharmacists practicing in hospital settings reported signs of burnout in 2016, 33 and 53% of health-system pharmacists exhibited high burnout on at least 1 subscale of the Maslach Burnout Inventory Human Services Survey (MBI-HSS).…”
mentioning
confidence: 99%
“… 30 Finally, we found that accessible training to improve the skills in the pharmacy workforce, sufficient time and a collaborative multidisciplinary approach are required to develop the community pharmacist role in this area, echoing previous research. 14 17 31 34 35 …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists’ work environments and the amount and type of work performed can influence pharmacists’ quality of work life [ 1 , 2 , 3 ] and their level of work performance [ 4 ]. Pharmacist “quality of work life” research has investigated a variety of constructs such as job stress, level of control, job satisfaction, commitment to their profession and their employing organization, work motivation, and role overload [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. These constructs have been associated with burnout, job turnover, and work performance and the findings have been used for improving pharmacist work systems, work processes, and patient safety [ 5 , 6 , 12 , 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%